2021
DOI: 10.3390/su132112037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change Impacts on the Hydroclimatic Response in Burundi Based on CMIP6 ESMs

Abstract: Burundi is susceptible to future water-related disasters, but examining the influence of climate change on regional hydroclimatic features is challenging due to a lack of local data and adaptation planning. This study investigated the influence of climate change on hydroclimate-focused changes in the climatology of heavy precipitation (and streamflow) means and extremes based on the multi-model ensemble mean of earth system models in the sixth phase of the Coupled Model Intercomparison Project (CMIP). For runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…We found a general increase in the average river discharge in North Burundi and a general decrease in South Burundi that agree with the anomalies found for precipitation in this study as well as by Kim et al (2021). The later concludes about the rise of seasonal mean and extreme runoff in the Ruvubu River Basin (station kag_290 in this study) as an effect of the intensification of the hydrological cycle, based on the projections from two earth system models in the sixth phase of the Coupled Model Intercomparison Project (CMIP6).…”
Section: Anomalies In Mean River Dischargesupporting
confidence: 92%
See 2 more Smart Citations
“…We found a general increase in the average river discharge in North Burundi and a general decrease in South Burundi that agree with the anomalies found for precipitation in this study as well as by Kim et al (2021). The later concludes about the rise of seasonal mean and extreme runoff in the Ruvubu River Basin (station kag_290 in this study) as an effect of the intensification of the hydrological cycle, based on the projections from two earth system models in the sixth phase of the Coupled Model Intercomparison Project (CMIP6).…”
Section: Anomalies In Mean River Dischargesupporting
confidence: 92%
“…Such studies relate mainly to the change in precipitation over the lake (Thiery et al, 2015(Thiery et al, , 2016, its water level (Tungaraza et al, 2012), or the stratification (Tierney et al, 2010). Yet, information about the responses in upstream basins, as represented by Burundi's network, is scarce (Kim et al, 2021;Ogiramoi Nyeko, 2011). One reason could be the difficulty to model this area due to the multiple swamps and high evaporation (Di Baldassarre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the increase in monthly peak for some months and change in the month in which the peak occurs agrees with the results of Xiang et al [45], who found a change in peak month from the month of August to July. In most past research studies, the largest change in flow values has been due to the higher emission scenario, but this study had a different outcome, which suggested higher values for the lower emission scenario [62]. This means that the likelihood of higher flooding is due to the SSP-126 emission scenario as opposed to the SSP-585 emission scenario.…”
Section: Future Projection Of Discharge Data Based On Cmip6 Modelmentioning
confidence: 64%
“…Distributed rainfall-runoff models have been used in numerous studies as predictive tools to assess the impact of different climate change projections on future water resource availability around the world [87][88][89]. In South Africa, the most comprehensive assessment includes the analysis of three different global circulation models (GCMs) (CNRM-CM3, ECHAM5/MPI-OM, IPSL-CM4), which, in combination with the A2 emission scenario, projected severe hydrological droughts for much of the Western Cape when comparing present and future conditions (1971-1990 and 2081-2100) [90].…”
Section: Uncertainties In Modelling Hydrological Changementioning
confidence: 99%